The Use of Digital Technology in the Processing and Interpretation of Assessment Data at the Primary School Level - Aini, Nurul; Amiani, Destin; Mutallaah, Indah; Yasin, Muhammad Hadi; Hasannah, Niswatun (Edupedia Publisher, 2025)
ABSTRACT This study aims to analyse the challenges, opportunities, and impacts of utilising digital technology in improving the quality of assessment in primary schools. The method used is qualitative with a Library Research and Integrative Review approach through a systematic review of scientific articles from Google Scholar, Scispace, DOAJ, and Scopus published between 2015 and 2025. Literature selection was carried out through identification, screening, and eligibility stages, then analysed using thematic analysis techniques to identify patterns and key findings related to the management and interpretation of assessment data. The results showed that digital technology plays a significant role in improving the efficiency, accuracy, and transparency of the assessment process through recording, processing, and automatic data visualisation. In addition, digital technology supports more accurate pedagogical decision-making through real-time data analysis. However, its implementation still faces challenges in the form of infrastructure limitations, variations in teachers' digital competencies, and data security issues. On the other hand, great opportunities arise from the potential of technology to realise objective, adaptive, and student-centred evaluation. Overall, the integration of digital technology has strategic potential to improve the quality of assessment in primary schools if implemented in a planned and sustainable manner.